2021
DOI: 10.3390/vetsci8010011
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Diseases of Staphylococcus pseudintermedius in Canines: Where to Next?

Abstract: Staphylococcus pseudintermedius is a pathogenic bacterium of concern within the veterinary sector and is involved in numerous infections in canines, including topical infections such as canine pyoderma and otitis externa, as well as systemic infections within the urinary, respiratory and reproductive tract. The high prevalence of methicillin-resistant Staphylococcus pseudintermedius (MRSP) within such infections is a growing concern. Therefore, it is crucial to understand the involvement of S. pseudintermedius… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
75
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(75 citation statements)
references
References 119 publications
(273 reference statements)
0
75
0
Order By: Relevance
“…Aside from the S. aureus nasal colonization in veterinarians, three studies reported the recovery of S. pseudintermedius from veterinarians of Denmark, Czech Republic, and Hong Kong, representing nasal colonization between 0.7–3.9%; interestingly, two of these studies recovered methicillin-resistant S. pseudintermedius (MRSP) isolates [ 138 , 139 ]. Dogs are frequently colonized and occasionally infected by this microorganism that could be transferred to in-contact humans, as is the case of veterinarians [ 209 ]. Several studies have isolated S. pseudintermedius from 46–92% of healthy dogs, with the highest prevalence at the perineum, followed by either the nasal or oral mucosa [ 210 , 211 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…Aside from the S. aureus nasal colonization in veterinarians, three studies reported the recovery of S. pseudintermedius from veterinarians of Denmark, Czech Republic, and Hong Kong, representing nasal colonization between 0.7–3.9%; interestingly, two of these studies recovered methicillin-resistant S. pseudintermedius (MRSP) isolates [ 138 , 139 ]. Dogs are frequently colonized and occasionally infected by this microorganism that could be transferred to in-contact humans, as is the case of veterinarians [ 209 ]. Several studies have isolated S. pseudintermedius from 46–92% of healthy dogs, with the highest prevalence at the perineum, followed by either the nasal or oral mucosa [ 210 , 211 ].…”
Section: Main Findings and Discussionmentioning
confidence: 99%
“…In humans, the most clinically important species is S. aureus, which is responsible for various infections including soft tissue infections [9] and pneumonia [10]. In dogs, the most important species is S. pseudintermedius [11] which causes mainly otitis and skin infections [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, the most important species is S . pseudintermedius [ 11 ] which causes mainly otitis and skin infections [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Staphylococcus pseudointermedius causes several diseases in canines, such as urinary tract infections, otitis externa, pyodermal infections, respiratory infections, and reproductive tract infections. Given the high prevalence of methicillin-resistant S. pseudointermedius strains, phage therapy is presented as a potentially successful alternative to treat these infections in canines [ 85 ] also due to the promising data shown in humans [ 86 ]. Several phages have been isolated against S. pseudointermedius .…”
Section: Phage Therapy In the Veterinary Fieldmentioning
confidence: 99%
“…Several phages have been isolated against S. pseudointermedius . In addition, the potential use of staphylococcal endolysins against S. pseudointermedius to treat infections caused by this pathogen has also been proposed [ 85 ].…”
Section: Phage Therapy In the Veterinary Fieldmentioning
confidence: 99%